PENGEMBANGAN TANAMAN PEMANIS STEVIA REBAUDIANA (BERTONI) DI EKOWISATA SUNGKAI PARK LAMBUNG BUKIT KECAMATAN PAUH KOTA PADANG - Elidahanum Husni; Dira Hefni; Dachriyanus Dachriyanus; Netty Suhatri; Meri Susanti (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
The human need for sugar as an additional ingredient to give sweet taste to food and drinks is very high. However, excessive consumption of sugar can cause problems, especially for people with obesity and diabetes. Therefore, an alternative sweetener is needed to replace sugar which does not have harmful effects on health and is low in calories, one of which is stevia sweetener. The purpose of this activity is for the community/medicinal plant farmers in the Sungkai Park Memorial Area to know about the types of plants that have health benefits such as the Stevia plant as a natural sweetener that can be consumed for health and can be stored for a long time. The activity was carried out at the Self-Help Agriculture and Rural Training Center (P4S) in Sungkai Village, Sungkai Green Park Ecotourism, Lambung Bukit Village, Padang City. This activity was carried out in three stages, namely: 1. counseling and training on how to make good quality traditional medicine namely Stevia, 2. practice of making Stevia leaf extract products, and 3. evaluation. The results of the implementation of the activity were that it could increase public awareness and awareness of the use of Stevia leaves in making health drinks. Stevia is obtained from the Stevia rebaudiana plant and is safe to consume in moderate doses of 0.1-4 mg per kilogram of body weight per day. stevia has many advantages compared to sugar, including 300 times sweeter than sucrose, does not damage teeth, can lower blood pressure and does not increase blood sugar levels. In addition, stevia can increase blood insulin levels, although the increase is relatively small. In addition to its use as a substitute for sugar as a sweetener. It is hoped that Stevia will become a natural sweetener that can be consumed for health and can be accepted by the market so that it can improve the community's economy, especially from the agricultural sector.